Risk perception of Ebola virus disease and COVID-19 among transport drivers living in Ugandan border districts - Blanco-Penedo, María José; Brindle, Hannah; Schmidt-Sane, Megan; Bowmer, Alex; Iradukunda, Constance; Mfitundinda, Herbert; Rwemisisi, Jude; Mukiibi, Grace Nicholas; Fricke, Christine; Carter, Simone; Kaawa-Mafigiri, David; Lees, Shelley (Frontiers in Public Health, 2023)
Background Cross-border movements between districts bordering Uganda and the Democratic Republic of Congo (DRC) are common due to the interdependence between populations on either side, though this increases the risk of the international spread of infectious diseases. Due to the nature of their work, boda boda drivers (motorcycle taxis), taxis and truck drivers continue to cross the border during epidemics. However, perceived risk of contracting and spreading communicable diseases may be influenced by several factors such as the level of education, packaging and perception of health care messages, limited interaction with local socio-cultural dynamics or personal experiences. This study aims to explore differences in movement patterns and risk perceptions as factors for transmission among transport drivers in Ugandan border districts during the 2018–2020 Ebola Virus Disease (EVD) epidemic and the current COVID-19 pandemic. Methods Between May and June 2021, in-depth interviews and focus group discussions were conducted with transport drivers in three Ugandan districts bordering DRC (Kasese, Kisoro and Hoima). Participants were asked about their knowledge and beliefs about EVD and COVID-19, perceived risk during epidemics, reasons for, and travel patterns during the EVD epidemic and COVID- 19 pandemic. A thematic content analysis was applied. Results Participants’ awareness of EVD was higher than that of COVID-19 however, the risk of transmission of Ebola virus was perceived as a remote threat. Measures restricting mobility during the COVID-19 pandemic had a greater impact on transport drivers compared to those implemented during the EVD epidemic, and were perceived as prohibitive rather than protective, largely due to fear of reprisals by security officers. Despite this, drivers were unlikely to be able to comply with the restrictions as they relied on their work as a source of income. Conclusion The vulnerabilities of transport drivers should be considered in the context of epidemics such EVD and COVID-19 in Uganda. Policy makers should address these particularities and assess the impact of public health measures on transport drivers’ mobility and involve them in designing of mobility-relatedpolicies.